2019
DOI: 10.1631/jzus.b1800211
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ regulates cell malignant growth via the c-Abl/HDAC2 signaling pathway in mammary epithelial cells

Abstract: Interferon-γ (IFN-γ) has been used to control cancers in clinical treatment. However, an increasing number of reports have suggested that in some cases effectiveness declines after a long treatment period, the reason being unclear. We have reported previously that long-term IFN-γ treatment induces malignant transformation of healthy lactating bovine mammary epithelial cells (BMECs) in vitro. In this study, we investigated the mechanisms underlying the malignant proliferation of BMECs under IFN-γ treatment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Recently it has been shown that IFN-γ can induce members of the Abelson (Abl) family of nonreceptor tyrosine kinases in certain cell types (73). Notably, Abl kinases are required for VEGF-and thrombin-induced disruption of adherens junctions, and imatinib is a potent inhibitor of Abl kinase activity (74,75).…”
Section: Induction Treatment and Evaluation Of Dss-induced Colitismentioning
confidence: 99%
“…Recently it has been shown that IFN-γ can induce members of the Abelson (Abl) family of nonreceptor tyrosine kinases in certain cell types (73). Notably, Abl kinases are required for VEGF-and thrombin-induced disruption of adherens junctions, and imatinib is a potent inhibitor of Abl kinase activity (74,75).…”
Section: Induction Treatment and Evaluation Of Dss-induced Colitismentioning
confidence: 99%
“…Proteasome is regarded as a multi-catalytic proteinase complex via eliminating intracellular damaged, misfolded, and short half-life functional proteins. It also plays a critical role in cell cycle control, apoptosis, and response to cell stress (Orlowski and Kuhn, 2008;Ren et al, 2019). Proteasome inhibitors have shown efficient anti-tumor activity both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…IFNs have been used with the intent to cure cancer for several years, including breast cancer (30). IFNs have been reported to exert antitumor effects by regulating the immune system and affecting cell proliferation and apoptosis (31). A limitation of the present study was failure to assess the influence of IFNs on UBA7 expression.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, retinoic acid has been demonstrated to induce UBA7 expression, which in turn induces ISGylation of promyelocytic leukaemia/retinoic acid receptor-α protein and causes degradation in acute promyelocytic leukaemia (29). Previous studies have reported that chemopreventive polyphenols (10,30,31), such as curcumin, epigallocatechin gallate and resveratrol, have the ability to influence UBA7 expression by altering the intracellular reactive oxygen species status, which is regulated via the c-Jun N-terminal kinase/nuclear factor erythroid 2-related factor 2 signaling pathway; however, this association exhibits dose-dependent effects (10). IFNs have been used with the intent to cure cancer for several years, including breast cancer (30).…”
Section: Discussionmentioning
confidence: 99%